DEVELOPING STUDENTS’ COMPETENCIES IN READING AND UNDERSTANDING TEXTS ON LINGUOCULTURAL STUDIES (Ustozlar uchun, 2025)
The development of students’ competencies in reading and understanding texts on linguocultural studies occupies a significant place in modern educational practice. With the increasing demand for multicultural communication and global integration, today’s learners encounter a variety of texts that are rooted in social and cultural contexts, which can present unique interpretative challenges. Literacy skills now extend beyond the boundaries of grammar and vocabulary, requiring learners to build nuanced comprehension abilities that incorporate cultural awareness, critical thinking, and context-sensitive analysis.